Brain‐specific monoallelic expression of bovine UBE3A is associated with genomic position. (17th November 2020) - Li, J.; Zhang, C.; Si, H.; Gu, S.; Liu, X.; Li, D.; Meng, S.; Yang, X.; Li, S.
Summary: Genomic imprinting is a rare epigenetic process in mammalian cells that leads to monoallelic expression of a gene with a parent‐specific pattern. The UBE3A (ubiquitin protein ligase E3A) gene is imprinted with maternal allelic expression in the brain but biallelically expressed in all other tissues in humans. The silencing of the paternal UBE3A allele is thought to be caused by the paternally expressed antisense RNA transcript of UBE3A‐ATS . The aberrant imprinted expression of the UBE3A is associated with several neurodevelopmental syndromes and psychological disorders. Cattle are a valuable model species in determining the genetic etiology of sporadic human disorder, and maternal expression of UEB3A has been revealed by next‐generation sequencing study in the bovine conceptus. In this study, we investigated the allelic expression of UBE3A and UBE3A‐ATS in adult bovine somatic tissues. To confirm the splicing pattern of bovine UBE3A, five 5′ alternative transcripts (MT210534–MT210538) were first obtained from bovine brain tissue by RT‐PCR. Based on 10 SNP genotypes, we found that the brain‐specific monoallelic expression of bovine UBE3A did not occur along the entire locus, and there was a shift from biallelic expression to monoallelic expression in exon 14 of the UBE3A gene. However, the brain‐specific monoallelic expression of bovine UBE3A‐ATS occurred in the entire gene. These observations demonstrated that the monoallelic expression did not occur along the bovine UBE3A entire locus and was associated with the genomic position.